Menanamkan Cinta Membaca melalui Program Literasi Bagi Siswa Kelas V SD Negeri 49 Kota Ternate - Bareki, Firda; Adam, Adiyana; Baharuddin, Baharuddin (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to describe the implementation of the Literacy Program in Building Reading Characters for grade V students of SD Negeri 49 Ternate City and its supporting and inhibiting factors. Using a qualitative descriptive approach, the study was conducted at SD Negeri 49 Ternate City with observation, interview, and documentation data collection techniques. The results show that the literacy program has been implemented since 2017 but has not run optimally. The stages of the program include habituation, development, and learning. Supporting factors include libraries, reading corners, motivational posters, and infrastructure facilities such as literacy huts and gazebos. However, inhibiting factors include students who are not fluent in reading and teacher delays in entering class that hinder reading literacy activities